Cyber Security in the Age of the Internet of Things, Constraints, and Solutions - Dickson, Solomon Makasda; OKECHUKWU, Ijeoma Peace (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
The Internet of Things (IoT) represents a paradigm shift in the way we interact with technology and the world around us. As the number of IoT devices continues to proliferate across various domains, ranging from smart homes to industrial settings, the vulnerabilities associated with this interconnected ecosystem become increasingly pronounced. This research aims to dissect the multifaceted challenges that arise in securing the vast network of interconnected devices, recognizing that the traditional approaches to cybersecurity may not suffice in this evolving environment. The objectives of the study are to comprehensively analyze these constraints, ranging from insecure IoT device configurations to potential data breaches and privacy concerns. The method adapted for this study is the V Model is a software development and testing methodology that emphasizes a structured approach to the development process. When applied to Cybersecurity and the Internet of Things (IoT) the V Model can be effectively utilized to address the unique complexities associated with securing interconnected devices. The adoption of a “security-by-design” philosophy emerges as a crucial aspect of mitigating IoT-related risks. Incorporating security measures from the inception of device development helps establish a robust foundation. The research anticipates contributing valuable insights to the ongoing discourse on cybersecurity, offering actionable recommendations for stakeholders navigating the intricate landscape of IoT security.